P140 Counselling for healthy lifestyle promotion in ageing healthcare personnel. (1st September 2016) - Piazza, Maria Francesca; Mereu, Noemi Maria; Spada, Laura; Mereu, Alessandra; Lai, Alberto; Galletta, Maura; Portoghese, Igor; Virgona, Patrizia; Campagna, Marcello
Abstract : The European Agency for Safety and Health at Work declared, for the next decades, an increase in the proportion of ageing workers. Thus, the health and the safety at work is necessary to ensure an active ageing through the promotion of healthy lifestyles, prevention of diseases and improvement of quality of life. Methods: From 09/2014 to 03/2016, a trained health visitor started a semi structural interview in a sample of 980 healthcare personnel (HCP) (mean age 46, range 18–68 years, SD ± 11.3) from five Italian hospitals. Information about dietary habits, physical activity, vaccination coverage, biological risk and exposure to biomechanical overload at work were collected. Information about health opportunities on all the variables analysed were provided for each participant during the counselling. Results: The 57% of HCP ate fruit and vegetables less than 3 times/day and 33% consumed meat more than 3 times per week. The 25% practiced physical activity less than 2 days/week. The 12% of HCP was vaccinated against influenza and 72% against hepatitis B. HCP did not know their antibody coverage status against varicella, measles, rubella, mumps and related occupational risks. The 19% of HCP reported a biological injury and the 18% of them did not follow the post exposure protocols. The 37% of HCP performed manual handling of patients. Among them, 26% and 43% had not available minor and major assistive devices, respectively. Discussion: The results suggest the need for a re-orientation process of services to protect ageing HCP in order to foster the adoption of healthy lifestyles and prevent occupational injuries and diseases. Ageing HCP's well-being represent a key point also in order to improve the quality of care in healthcare settings. The study was conducted with the financial support of the Italian Ministry of Health, CCM Program 2013.